Coding art a guide to unlocking your creativity with the processing language and p5.js in four simple steps - Funk, Mathias; Zhang, Yu (Design thinking, 2024)
Finally, a book on creative programming, written directly for artists and designers! This second edition offers expanded and updated content incorporating the latest advancements and trends in the field of creative programming, also for creatives who want to work directly with P5.js and online. It delves deeper into the intricacies of computational art. It includes fresh case studies that explore real-world applications of coding art, inspiring readers to think beyond traditional boundaries. Rather than following a computer science curriculum, this book is aimed at creatives who are working in the intersection of design, art, and education. Following a real-world use case of computation art, you'll see how it relates back to the four key pillars, and addresses potential pitfalls and challenges in the creative process. All code examples are presented in a fully integrated Processing example library, making it easy for readers to get started. This unique and finely balanced approach between skill acquisition and development makes Coding Art, Second Edition the ideal reference book for both creative programming and the creative process for professors and students alike.